I'd like to show that the linear functions $$ \varphi(z) = z+b, \;\;\; 0\neq b\in \mathbb{C}$$ $$ \psi(z) = -z+c, \;\;\; c\in \mathbb{C}$$ generate, under composition, a group isomorphic to $Dih_\infty$, the infinite dihedral group.

Now $Dih_\infty$ may be presented as follows: $$ \langle r,s \, | \, s^2=1, srs=r^{-1}\rangle.$$

These relations are satisfied by $\varphi$ and $\psi$, since $\psi^2 = 1$, ($1$ stands for the identity function) and $\psi\circ \varphi \circ \psi = \varphi^{-1}$. How do I show no further relations hold ?

An alternative proof is also welcome.


An idea:



And clearly, $\;\phi=\psi^{-1}\tau=\psi\tau\;$ , thus our group is

$$\langle\;\psi\,,\,\tau\;;\;\psi^2=\tau^2=1\;\rangle=C_2*C_2\cong Dih_\infty$$

Of course, in order to be completely formal (or perhaps "too" formal) you may want to show that no finite product of the for $\,a_1b_1a_2b_2\cdot\ldots\cdot\;$ , with $\,a_i,b_i\in\{\psi\,,\,\tau\}\,\,,\,\,a_i\neq b_i\;$ , can be the identity map (trivial element) , but I think this is almost "trivial", since

$$\tau\circ\psi(z)=\tau(-z+c)=-(-z+c)+c-b=z-b\neq z\;,\;\;\text{since}\;\;b\neq 0$$

$$\text{and as already noted above,}\;\;\psi\circ\tau(z)=\psi(-z+c-b)=-(-z+c-b)+c=z+b\neq z$$

  • $\begingroup$ Thank you for your answer. You are correct in stating that the relations $\psi^2=\tau^1=1$ hold. Still, as you mention, one must show that no further relations hold. How does that follow from the statements $\tau \psi\neq 1$ and $\psi\tau \neq 1$ ? $\endgroup$ – Teddy Jun 11 '13 at 5:58
  • $\begingroup$ Induction, @Teddy. Note that any normal element in that free product $\,C_2*C_2\,$ is a finite product (or concatenation, if you will) of pairs of the form $\,\tau\psi\;,\;\psi\tau\,$ and/or one more element, for example: $$\tau\psi\tau\;,\;\;\psi\tau\psi\tau\psi\;,\;\tau\;,etc.$$ $\endgroup$ – DonAntonio Jun 11 '13 at 6:01

Without loss of generality, you can assume that $b=1$ and $c=0$.

Let $G$ be the group generated by $\phi$ and $\psi$. You know there is a surjection $f:D_\infty\to G$. Using the relations defining $D_\infty$ one can check easily that every element $g$ of $D_\infty$ is of the form $s^ar^b$ with $0\leq a<2$ and $b\in\mathbb Z$.

If $f(g)$ is the identity, then $f(g)(\sqrt{-1})=\sqrt{-1}$. Show that in that case $a=b=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.